A generalized modelling approach to assess climate influences on hand, foot, and mouth disease in East Coast Malaysia - Nurmarni Athirah Abdul Wahid,; Jamaludin Suhaila,; Haliza Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Hand, foot, and mouth disease (HFMD) outbreaks in Asia have increased since the late 1990s, causing severe and often fatal consequences. Several statistical approaches, such as Generalized Linear Models (GLM) and Generalized Additive Models (GAM), have been used in numerous studies to examine the association between climate factors and HFMD cases. However, the results vary by country. In Malaysia, these issues require further research, as there are only a few studies employing GLM and GAM approaches that focus on HFMD cases and climate factors, particularly in the East Coast region. Therefore, this study explores the association between HFMD and climate factors on Malaysia's East Coast using GLM and GAM with Negative Binomial to identify the best model for interpreting HFMD cases. The findings show that climate factors affect HFMD differently across states in East Coast Malaysia. The results show that the GAM Negative Binomial model best represents these issues. The temperatures between 26°C and 28°C will decrease the risk of HFMD cases in Pahang over the next two weeks. Besides, temperatures ranging from 25 to 27°C and 28.5 to 30°C significantly increased HFMD risk in Terengganu over the next two weeks. Nevertheless, Kelantan found no correlation between climate and HFMD. These findings can help local health authorities in developing a climate-based early warning system to minimize HFMD outbreaks in Malaysia's East Coast Region.